Challenges in implementing a small-scale farmers’ capacity-building program: The case of the food production, processing, and marketing project in the Democratic Republic of Congo - Ragasa, Catherine; Nkonya, Ephraim M.; Ulimwengu, John M.; Randriamamonjy, Josee (International Food Policy Research Institute, 2016)
In 2011, in collaboration with the United States Agency for International Development (USAID), the Democratic Republic of Congo’s government launched the Food Production, Processing, and Marketing project—which aimed to raise incomes and improve food security in the target areas by improving agricultural productivity, market efficiency, and the capacity of producers to respond to market signals. In August–October 2013 and February–March 2014, halfway through the project’s implementation, a midline survey was conducted to assess progress with respect to intermediate outcomes. The present paper highlights the results of that assessment survey. We pay close attention to accurate attribution of observed changes to the project and employ a double-difference method that compares the changes in indicators before the project and at the time of the survey (project midline) between the beneficiaries and comparable control groups. Overall, the survey results suggest weak impact on most of the outcome indicators, and they highlight challenges in implementing small-scale farmers’ capacity building within the context of weak institutions and a fragile political context.